The basis of plants adoption and it's application in landscape of Malay traditional house - Nur Hafizah Ramle; Ab. Aziz Shuaib; Ramle Abdullah,; Olalere, Folasayo Enoch; Mohd Sukhairi Mat Rasat (2015)
Malay home surroundings is varies in plants pattern as well as a variety of size. The plants species cultivated own their particular reasons. Malay house environment is so harmony with humans, Mother Nature also culture relationship has visualise a unique environmental design. In this accomplishing research, it will provide an understanding of plants adoption of Malay house environment. Environment factor and socio-culture dominates planting pattern of Malay house environment. The cultivated plant species purpose is not only for beautifying the view only but also involve food, medicine, cosmetic, belief and also aesthetic values factor. This research use Paine and Taylor approach that emphasize four factors of nature, culture, view and meaning to obtain wider range of vision from informants in this field to provide a wider point of understanding in comprehending plants adoption pattern. The environment of Malay society life is much near with Mother Nature has influence plants landscape pattern at their home yard/ lawn. The plants selection planted were much influenced with Malay society’s lifestyle.